Tempo de observação e resolução espontânea de fimose primária em crianças - De Arruda Lourenção, Pedro Luiz Toledo [UNESP]; Queiroz, Dênis Silva [UNESP]; De-Oliveira Junior, Wilson Elias [UNESP]; Comes, Giovana Tuccille [UNESP]; Marques, Rozemeire Garcia [UNESP]; Jozala, Débora Rodrigues [UNESP]; Ortolan, Erika Veruska Paiva [UNESP] (FapUNIFESP (SciELO), 2017)
Objective: to investigate spontaneous resolution rate of a series of patients with physiologic phimosis in relation to observation time and presence of symptoms. Methods: retrospective and longitudinal follow-up study of patients with physiologic phimosis, that did not apply topic treatment. These patients were invited for a new visit for reevaluation, or recent data were obtained by chart analysis. Spontaneous resolution rate was determined and statistically compared to age, presence of symptoms at first medical visit and time until reevaluation. Results: seventy one patients were included. Medium time of observation from first visit to reevaluation was 37.4 months. There was spontaneous resolution of phimosis in 32 (45%) patients. Children with spontaneous resolution were younger at initial diagnosis and were observed during a longer period of time. Most asymptomatic patients at first visit presented spontaneous resolution. However, it was not possible to stablish a significant relationship between presence of symptoms and evolution of physiologic phimosis. Conclusions: time of observation was the main determinant of spontaneous resolution of patients with physiologic phimosis, reinforcing the current more conservative approach regarding circumcision of those patients.
Observation time and spontaneous resolution of primary phimosis in children
Keywords: Child; Circumcision; Male; Phimosis